Beyond the "Iron triangle" of scope, time & costs : managing uncertainties in big construction projects in different contexts : a comparative study of big construction projects in Ukraine and Norway - Iermolenko, Olga (Universitetet i Nordland, 2011)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2011